How would you define map and filter using foldr in Haskell? - haskell

I'm doing a bit of self study on functional languages (currently using Haskell). I came across a Haskell based assignment which requires defining map and filter in terms of foldr. For the life of me I'm not fully understanding how to go about this.
For example when I define a map function like:
map' :: (a -> b) -> [a] -> [b]
map' f [] = []
map' f (x:xs) = foldr (\x xs -> (f x):xs) [] xs
I don't know why the first element of the list is always ignored. Meaning that:
map' (*2) [1,2,3,4]
results in [4,6,8] instead of [2,4,6,8]
Similarly, my filter' function:
filter' :: (a -> Bool) -> [a] -> [a]
filter' p [] = []
filter' p (x:xs) = foldr (\x xs -> if p x then x:xs else xs ) [] xs
when run as:
filter' even [2,3,4,5,6]
results in [4,6] instead of [2,4,6]
Why would this be the case? And how SHOULD I have defined these functions to get the expected results? I'm assuming something is wrong with my lambda expressions...

I wish I could just comment, but alas, I don't have enough karma.
The other answers are all good ones, but I think the biggest confusion seems to be stemming from your use of x and xs.
If you rewrote it as
map' :: (a -> b) -> [a] -> [b]
map' f [] = []
map' f (x:xs) = foldr (\y ys -> (f y):ys) [] xs
you would clearly see that x is not even mentioned on the right-hand side, so there's no way that it could be in the solution.
Cheers

For your first question, foldr already has a case for the empty list, so you need not and should not provide a case for it in your own map.
map' f = foldr (\x xs -> f x : xs) []
The same holds for filter'
filter' p = foldr (\x xs -> if p x then x : xs else xs) []
Nothing is wrong with your lambda expressions, but there is something wrong with your definitions of filter' and map'. In the cons case (x:xs) you eat the head (x) away and then pass the tail to foldr. The foldr function can never see the first element you already ate. :)
Alse note that:
filter' p = foldr (\x xs -> if p x then x : xs else xs) []
is equivalent (η-equivalent) to:
filter' p xs = foldr (\x xs -> if p x then x : xs else xs) [] xs

I would define map using foldr and function composition as follows:
map :: (a -> b) -> [a] -> [b]
map f = foldr ((:).f) []
And for the case of filter:
filter :: (a -> Bool) -> [a] -> [a]
filter p = foldr (\x xs -> if p x then x:xs else xs) []
Note that it is not necessary to pass the list itself when defining functions over lists using foldr or foldl.
The problem with your solution is that you drop the head of the list and then apply the map over the list and
this is why the head of the list is missing when the result is shown.

In your definitions, you are doing pattern matching for x:xs, which means, when your argument is [1,2,3,4], x is bound to 1 and xs is bound to the rest of the list: [2,3,4].
What you should not do is simply throw away x: part. Then your foldr will be working on whole list.
So your definitions should look as follows:
map' :: (a -> b) -> [a] -> [b]
map' f [] = []
map' f xs = foldr (\x xs -> (f x):xs) [] xs
and
filter' :: (a -> Bool) -> [a] -> [a]
filter' p [] = []
filter' p xs = foldr (\x xs -> if p x then x:xs else xs ) [] xs

I am new to Haskell (in fact I've found this page asking the same question) but this is my understanding of lists and foldr so far:
lists are elements that are linked to the next element with the cons (:) operator. they terminate with the empty list []. (think of it as a binary operator just like addition (+) 1+2+3+4 = 10, 1:2:3:4:[] = [1,2,3,4]
foldr function takes a function that takes two parameters. this will replace the cons operator, which will define how each item is linked to the next.
it also takes the terminal value for the operation, which can be tought as the initial value that will be assigned to the empty list. for cons it is empty list []. if you link an empty list to any list the result is the list itself. so for a sumfunction it is 0. for a multiply function it is 1, etc.
and it takes the list itself
So my solution is as follows:
filter' p = foldr (\x n -> if p x then x : n else n) []
the lambda expression is our link function, which will be used instead of the cons (:) operator. Empty list is our default value for an empty list. If predicate is satisfied we link to the next item using (:) as normal, else we simply don't link at all.
map' f = foldr (\x n -> f x : n) []
here we link f x to the next item instead of just x, which would simply duplicate the list.
Also, note that you don't need to use pattern matching, since we already tell foldr what to do in case of an empty list.
I know this question is really old but I just wanted to answer it anyway. I hope it is not against the rules.

A different way to think about it - foldr exists because the following recursive pattern is used often:
-- Example 1: Sum up numbers
summa :: Num a => [a] -> a
summa [] = 0
summa (x:xs) = x + suma xs
Taking the product of numbers or even reversing a list looks structurally very similar to the previous recursive function:
-- Example 2: Reverse numbers
reverso :: [a] -> [a]
reverso [] = []
reverso (x:xs) = x `op` reverso xs
where
op = (\curr acc -> acc ++ [curr])
The structure in the above examples only differs in the initial value (0 for summa and [] for reverso) along with the operator between the first value and the recursive call (+ for summa and (\q qs -> qs ++ [q]) for reverso). So the function structure for the above examples can be generally seen as
-- Generic function structure
foo :: (a -> [a] -> [a]) -> [a] -> [a] -> [a]
foo op init_val [] = init_val
foo op init_val (x:xs) = x `op` foo op init_val xs
To see that this "generic" foo works, we could now rewrite reverso by using foo and passing it the operator, initial value, and the list itself:
-- Test: reverso using foo
foo (\curr acc -> acc ++ [curr]) [] [1,2,3,4]
Let's give foo a more generic type signature so that it works for other problems as well:
foo :: (a -> b -> b) -> b -> [a] -> b
Now, getting back to your question - we could write filter like so:
-- Example 3: filter
filtero :: (a -> Bool) -> [a] -> [a]
filtero p [] = []
filtero p (x:xs) = x `filterLogic` (filtero p xs)
where
filterLogic = (\curr acc -> if (p curr) then curr:acc else acc)
This again has a very similar structure to summa and reverso. Hence, we should be able to use foo to rewrite it. Let's say we want to filter the even numbers from the list [1,2,3,4]. Then again we pass foo the operator (in this case filterLogic), initial value, and the list itself. filterLogic in this example takes a p function, called a predicate, which we'll have to define for the call:
let p = even in foo (\curr acc -> if (p curr) then curr:acc else acc) [] [1,2,3,4]
foo in Haskell is called foldr. So, we've rewritten filter using foldr.
let p = even in foldr (\curr acc -> if (p curr) then curr:acc else acc) [] [1,2,3,4]
So, filter can be written with foldr as we've seen:
-- Solution 1: filter using foldr
filtero' :: (a -> Bool) -> [a] -> [a]
filtero' p xs = foldr (\curr acc -> if (p curr) then curr:acc else acc) [] xs
As for map, we could also write it as
-- Example 4: map
mapo :: (a -> b) -> [a] -> [b]
mapo f [] = []
mapo f (x:xs) = x `op` (mapo f xs)
where
op = (\curr acc -> (f curr) : acc)
which therefore can be rewritten using foldr. For example, to multiply every number in a list by two:
let f = (* 2) in foldr (\curr acc -> (f curr) : acc) [] [1,2,3,4]
So, map can be written with foldr as we've seen:
-- Solution 2: map using foldr
mapo' :: (a -> b) -> [a] -> [b]
mapo' f xs = foldr (\curr acc -> (f curr) : acc) [] xs

Your solution almost works .)
The problem is that you've got two differend bindings for x in both your functions (Inside the patternmatching and inside your lambda expression), therefore you loose track of the first Element.
map' :: (a -> b) -> [a] -> [b]
map' f [] = []
map' f (x:xs) = foldr (\x xs -> (f x):xs) [] (x:xs)
filter' :: (a -> Bool) -> [a] -> [a]
filter' p [] = []
filter' p (x:xs) = foldr (\x xs -> if p x then x:xs else xs ) [] (x:xs)
This should to the trick :). Also: you can write your functions pointfree style easily.

*Main> :{
*Main| map' :: (a -> b) -> [a] -> [b]
*Main| map' = \f -> \ys -> (foldr (\x -> \acc -> f x:acc) [] ys)
*Main| :}
*Main> map' (^2) [1..10]
[1,4,9,16,25,36,49,64,81,100]
*Main> :{
*Main| filter' :: (a -> Bool) -> [a] -> [a]
*Main| filter' = \p -> \ys -> (foldr (\x -> \acc -> if p x then x:acc else acc) [] ys)
*Main| :}
*Main> filter' (>10) [1..100]
In the above snippets acc refers to accumulator and x refers to the last element.

Everything is correct in your lambda expressions. The problem is you are missing the first element in the list. If you try,
map' f (x:xs) = foldr (\x xs -> f x:xs) [] (x:xs)
then you shouldn't miss the first element anymore. The same logic applies to filter.
filter' p (x:xs) = foldr(\ y xs -> if p y then y:xs else xs) [] (x:xs)

Related

Haskell concat / filter according specific rules

According to following rules, I tried to solve the following problem:
No definition of recursion
No List of Comprehension
Only Prelude-Module is allowed.
Now I have to implement higher-order for concat and filter.
Im at this point:
concat' :: [[a]] -> [a]
concat' a = (concat a)
filter' :: (a -> Bool) -> [a] -> [a]
filter' p [] = []
filter' p (x:xs)
| p x = x : filter p xs
| otherwise = filter p xs
The concat function is working (nothing special so far) -> Is that a defined recursion? I mean I use the predefined concat from standard-prelude but myself I don't define it - or am I wrong?
For the filter, the function I've looked up the definition of standard prelude but that's either not working and it contains a definition of recursion.
I'm supposing the concat and filter functions should be avoided. Why would we need to implement concat and filter if they're already available? So try implementing them from scratch.
We can use folding instead of recursion and list comprehensions. The below solutions use the function foldr.
foldr :: Foldable t => (a -> b -> b) -> b -> t a -> b
concat' :: [[a]] -> [a]
concat' = foldr (++) []
filter' :: (a -> Bool) -> [a] -> [a]
filter' p = foldr (\x acc -> if p x then x:acc else acc) []
Examples:
main = do
print $ concat' ["A", "B", "CAB"] -- "ABCAB"
print $ filter' (\x -> x `mod` 2 == 0) [1..9] -- [2, 4, 6, 8]
You may do as follows;
concat' :: Monad m => m (m b) -> m b
concat' = (id =<<)
filter' p = ((\x-> if p x then [x] else []) =<<)
=<< is just flipped version of the monadic bind operator >>=.
filter' (< 10) [1,2,3,10,11,12]
[1,2,3]

Can my implementation of filter be improved?

An exercise in Haskell from First Principles says to implement filter using foldr and this is what I came up with but it feels and looks clunky. Is there a more natural way to implement it with a foldr?
import Data.Bool
myFilter :: (a -> Bool) -> [a] -> [a]
myFilter f = foldr (\x -> bool (++ []) ((:) x) (f x)) []
I would only use bool if it let me get rid of the lambda expression simply, by composing a call to bool with the predicate p: bool iffalse iftrue . p. However, p isn't the only function that needs to be called on a list element; (:) does as well. You could use the Applicative instance for functions, to write
myfilter p = foldr (bool id . (:) <*> p) [] -- yuck
but in this case I would just use a plain if expression, inside the lambda expression:
myfilter p = foldr (\x -> if p x then (x:) else id) [] -- much clearer!
Note that when specialized to functions, the Applicative's (<*>) operator is defined as f <*> g = \x -> f x (g x). I leave it as an exercise to use that definition to transform bool id . (:) <*> p into
\x -> bool id (x:) (p x).
You can use the Applicative instance of (->) a to make the lambda cleaner. But, if you want to use foldr, I don't think there's any substantial change you can effect:
myFilter f = foldr (bool id <$> (:) <*> f) []
bool id <$> (:) <*> f means \x -> bool id ((:) x) (f x). bool id has type ([a] -> [a]) -> Bool -> ([a] -> [a]). (:) has type a -> [a] -> [a], and f has type a -> Bool. When (<$>) and (<*>) are used in this way, you can think of it as pretending that (:) and f don't have an a argument, making them [a] -> [a] and Bool, respectively, applying them to bool id to get a [a] -> [a], and then ending the lie by reintroducing the a argument, making a a -> [a] -> [a]. The operators are in charge of threading that a around, so you don't need a lambda abstraction.
Rather than merely searching for a more elegant implementation, it would might help you more to learn an elegant process of searching for an implementation. This should make it simpler to find elegant solutions.
For any function h on lists we have that,
h = foldr f e
if and only if
h [] = e
h (x:xs) = f x (h xs)
In this case your h is filter p for some boolean function p that selects which elements to keep. Implementing filter p as a "simple" recursive function is not too hard.
filter p [] = []
filter p (x:xs) = if p x then x : (filter p xs) else (filter p xs)
The 1st line implies e = []. The 2nd line needs to be written in the form f x (filter p xs) to match the equation of h above, in order for us to deduce which f to plug in the foldr. To do that we just abstract over those two expressions.
filter p [] = []
filter p (x:xs) = (\x ys -> if p x then x : ys else ys) x (filter p xs)
So we have found that,
e = []
f x ys = if p x then x: ys else ys
It therefore follows,
filter p = foldr (\y ys -> if p y then y : ys else ys) []
To learn more about this method of working with foldr I recommend reading
"A tutorial on the universality and expressiveness of fold" by Graham Hutton.
Some added notes:
In case this seems overly complicated, note that while the principles above can be used in this "semi rigorous" fashion via algebraic manipulation, they can and should also be used to guide your intuition and aid you in informal development.
The equation for h (x:xs) = f x (h xs) sheds some clarity on how to find f. In the case where h is the filtering function you want an f which combines the element x with a tail that has already been filtered. If you really understand this it should be easy to arrive at,
f x ys = if p x then x : ys else ys
Yes, there is:
myFilter :: (a -> Bool) -> [a] -> [a]
myFilter f = foldMap (\x -> [x | f x])
> myFilter even [1..10]
[2,4,6,8,10]
See, I switched it on you, with foldMap.
Well, with foldr it is foldr (\x -> ([x | f x] ++)) [].

How to apply a function to a specific element of a list

How can I apply a function to only a single element of a list?
Any suggestion?
Example:
let list = [1,2,3,4,3,6]
function x = x * 2
in ...
I want to apply function only to the first occurance of 3 and stop there.
Output:
List = [1,2,6,4,3,6] -- [1, 2, function 3, 4, 3, 6]
To map or not to map, that is the question.
Better not to map.
Why? Because map id == id anyway, and you only want to map through one element, the first one found to be equal to the argument given.
Thus, split the list in two, change the found element, and glue them all back together. Simple.
See: span :: (a -> Bool) -> [a] -> ([a], [a]).
Write: revappend (xs :: [a]) (ys :: [a]) == append (reverse xs) ys, only efficient.
Or fuse all the pieces together into one function. You can code it directly with manual recursion, or using foldr. Remember,
map f xs = foldr (\x r -> f x : r) [] xs
takeWhile p xs = foldr (\x r -> if p x then x : r else []) [] xs
takeUntil p xs = foldr (\x r -> if p x then [x] else x : r) [] xs
filter p xs = foldr (\x r -> if p x then x : r else r) [] xs
duplicate xs = foldr (\x r -> x : x : r) [] xs
mapFirstThat p f xs = -- ... your function
etc. Although, foldr won't be a direct fit, as you need the combining function of the (\x xs r -> ...) variety. That is known as paramorphism, and can be faked by feeding tails xs to the foldr, instead.
you need to maintain some type of state to indicate the first instance of the value, since map will apply the function to all values.
Perhaps something like this
map (\(b,x) -> if (b) then f x else x) $ markFirst 3 [1,2,3,4,3,6]
and
markFirst :: a -> [a] -> [(Boolean,a)]
markFirst a [] = []
markFirst a (x:xs) | x==a = (True,x): zip (repeat False) xs
| otherwise = (False,x): markFirst a xs
I'm sure there is an easier way, but that's the best I came up with at this time on the day before Thanksgiving.
Here is another approach based on the comment below
> let leftap f (x,y) = f x ++ y
leftap (map (\x -> if(x==3) then f x else x)) $ splitAt 3 [1,2,3,4,3,6]
You can just create a simple function which multiples a number by two:
times_two :: (Num a) => a -> a
times_two x = x * 2
Then simply search for the specified element in the list, and apply times_two to it. Something like this could work:
map_one_element :: (Eq a, Num a) => a -> (a -> a) -> [a] -> [a]
-- base case
map_one_element _ _ [] = []
-- recursive case
map_one_element x f (y:ys)
-- ff element is found, apply f to it and add rest of the list normally
| x == y = f y : ys
-- first occurence hasnt been found, keep recursing
| otherwise = y : map_one_element x f ys
Which works as follows:
*Main> map_one_element 3 times_two [1,2,3,4,3,6]
[1,2,6,4,3,6]

How to pattern match the end of a list?

Say I wanted to remove all zeros at the end of a list:
removeEndingZeros :: (Num a, Eq a) => [a] -> [a]
removeEndingZeros (xs ++ [0]) = removeEndingZeros xs
removeEndingZeros xs = xs
This does not work because of the (++) operator in the argument. How can I determine the end of a list through pattern-matching?
There is a function in Data.List to do this:
dropWhileEnd :: (a -> Bool) -> [a] -> [a]
dropWhileEnd p = foldr (\x xs -> if p x && null xs then [] else x : xs) []
So you can drop the trailing zeros with
dropWhileEnd (== 0)
Another, very similar, function can be implemented like this:
dropWhileEnd2 :: (a -> Bool) -> [a] -> [a]
dropWhileEnd2 p = foldr (\x xs -> if null xs && p x then [] else x : xs) []
dropWhileEnd2 p has exactly the same semantics as reverse . dropWhile p . reverse, but can reasonably be expected to be faster by a constant factor. dropWhileEnd has different, non-comparable strictness properties than the others (it's stricter in some ways and less strict in others).
Can you figure out circumstances under which each can be expected to be faster?

Haskell multifilter

I want to filter a list by predicates curried from another list.
For instance:
multifilter :: (a -> a -> Bool) -> [a] -> [a] -> [a]
multifilter _ _ [] = []
multifilter _ [] _ = []
multifilter f (x:xs) ys = (filter (f x) ys) ++ (multifilter f xs ys)
With usage such as:
prelude> multifilter (==) [1,2,3] [5,3,2]
[2,3]
Is there a standard way to do this?
You can use intersectBy:
λ> :t intersectBy
intersectBy :: (a -> a -> Bool) -> [a] -> [a] -> [a]
λ> intersectBy (==) [1,2,3] [5,3,2]
[2,3]
You can use hoogle to search functions using type signature and finding them.
Note: This answer implements the specification expressed by the words and example in the question, rather than the different one given by the implementation of multifilter there. For the latter possibility, see gallais' answer.
Sibi's answer shows how you should actually do it. In any case, it is instructive to consider how you might write your function using filter. To begin with, we can establish two facts about it:
multifilter can be expressed directly as filter pred for some appropriate choice of pred. Given a fixed "predicate list", whether an element of the list you are multifiltering will be in the result only depends on the value of that element.
In multifilter f xs ys, the list you are filtering is xs, and the "predicate list" is ys. Were it not so, you would get [3,2] rather than [2,3] in your (quite well-chosen) example.
So we have:
multifilter :: (a -> a -> Bool) -> [a] -> [a] -> [a]
multifilter f xs ys = filter pred xs
where
pred = undefined -- TODO
All we need to do is implementing pred. Given an element x, pred should produce True if, for some element y of ys, f x y is true. We can conveniently express that using any:
pred x = any (\y -> f x y) ys
-- Or, with less line noise:
pred x = any (f x) ys
Therefore, multifilter becomes...
multifilter :: (a -> a -> Bool) -> [a] -> [a] -> [a]
multifilter f xs ys = filter pred xs
where
pred x = any (f x) ys
-- Or, more compactly:
multifilter :: (a -> a -> Bool) -> [a] -> [a] -> [a]
multifilter f xs ys = filter (\x -> any (f x) ys) xs
... which is essentially equivalent to intersectBy, as you can see by looking at intersectBy's implementation.
A third option is to use a list comprehension:
multifilter rel xs ys = [ x | x <- xs, y <- ys, x `rel` y ]
or, if you want partial application:
multifilter p xs ys = [ x | x <- xs, let f = p x, y <- ys, f y ]
If you want to use filter,
relate rel xs ys = filter (uncurry rel) $ liftM2 (,) xs ys
(and throw in map fst)
The answer you have accepted provides a function distinct from the one defined in your post: it retains elements from xs when yours retains elements from ys. You can spot this mistake by using a more general type for multifilter:
multifilter :: (a -> b -> Bool) -> [a] -> [b] -> [b]
Now, this can be implemented following the specification described in your post like so:
multifilter p xs ys = fmap snd
$ filter (uncurry p)
$ concatMap (\ x -> fmap (x,) ys) xs
If you don't mind retaining the values in the order they are in in ys then you can have an even simpler definition:
multifilter' :: (a -> b -> Bool) -> [a] -> [b] -> [b]
multifilter' p xs = filter (flip any xs . flip p)
Simply use Hoogle to find it out via the signature (a -> a -> Bool) -> [a] -> [a] -> [a]
https://www.haskell.org/hoogle/?hoogle=%28a+-%3E+a+-%3E+Bool%29+-%3E+%5Ba%5D+-%3E+%5Ba%5D+-%3E+%5Ba%5D
yields intersectBy:
intersectBy :: (a -> a -> Bool) -> [a] -> [a] -> [a]

Resources